Implementation and Operational Research: Maternal Combination Antiretroviral Therapy Is Associated With Improved Retention of HIV-Exposed Infants in Kinshasa, Democratic Republic of Congo. (1st July 2015) - Feinstein, Lydia; Edmonds, Andrew; Okitolonda, Vitus; Cole, Stephen R.; Van Rie, Annelies; Chi, Benjamin H.; Ndjibu, Papy; Lusiama, Jean; Chalachala, Jean L.; Behets, Frieda
Abstract : Background: Programs to prevent mother-to-child HIV transmission are plagued by loss to follow-up (LTFU) of HIV-exposed infants. We assessed if providing combination antiretroviral therapy (cART) to HIV-infected mothers was associated with reduced LTFU of their HIV-exposed infants in Kinshasa, DR Congo. Methods: We constructed a cohort of mother–infant pairs using routinely collected clinical data. Maternal cART eligibility was based on national guidelines in effect at the time. Infants were considered LTFU after 3 failed tracking attempts after a missed visit or if more than 6 months passed since they were last seen in clinic. Statistical methods accounted for competing risks (eg, death). Results: A total of 1318 infants enrolled at a median age of 2.6 weeks (interquartile range: 2.1–6.9), at which point 24% of mothers were receiving cART. Overall, 5% of infants never returned to care after enrollment and 18% were LTFU by 18 months. The 18-month cumulative incidence of LTFU was 8% among infants whose mothers initiated cART by infant enrollment and 20% among infants whose mothers were not yet on cART. Adjusted for baseline factors, infants whose mothers were not on cART were over twice as likely to be LTFU, with a subdistribution hazard ratio of 2.75 (95% confidence limit: 1.81 to 4.16). The association remained strong regardless of maternal CD4 count at infant enrollment. Conclusions: Increasing access to cART for pregnant women could improve retention of HIV-exposed infants, thereby increasing the clinical and population-level impacts of prevention of mother-to-child HIV transmission interventions and access to early cART for HIV-infected infants.